A Primary Amebic Meningoencephalitis Case Associated with Rafting on an Artificial Whitewater River. (4th October 2017) - Cope, Jennifer; Murphy, Jennifer; Kahler, Amy; Gorbett, Daniel; Ali, Ibne; Taylor, Brandi; Corbitt, Lisa; Roy, Shantanu; Lee, Nicole; Roellig, Dawn; Brewer, Scott; Hill, Vincent
Abstract: Background: Naegleria fowleri is a climate-sensitive thermophilic ameba found in freshwater that causes primary amebic meningoencephalitis (PAM; 0–8 infections per year in the U.S.) when it enters the nose and migrates to the brain. Patient exposure to water containing the ameba typically occurs in warm freshwater lakes and ponds during recreational water activities. In June 2016, an 18-year-old woman died of PAM after traveling to North Carolina, where she participated in whitewater rafting on an artificial whitewater river. Methods: To determine water exposures, we reviewed medical records and conducted interviews with family and individuals who had traveled with the case-patient. To further investigate the artificial whitewater river as a possible exposure source, we visited the whitewater facility and collected water, biofilm, and sediment samples from the facility and from the nearby natural river. We performed select water quality tests onsite and tested for the presence of N. fowleri by culture and real-time PCR in the laboratory. Results: Interviews revealed that the case-patient's most probable water exposure in the 10 days before becoming ill occurred while rafting on an artificial whitewater river during which she was thrown out of the raft and submerged underwater. The ~11.5 million gallons of water in the whitewater facility were filtered, subjected to UV light, and occasionally chlorinated. Heavy algal growth was noted. The free chlorine residual was 0.05 mg/L, turbidity was 6.7 NTU, and water temperature was 30°C in the whitewater facility during the site visit. All 11 water-related samples taken from the facility were positive for N. fowleri . Of 5 samples taken from the natural river, 1 sediment sample was positive for N. fowleri . Conclusion: This investigation documents a novel exposure to an artificial whitewater river as the likely exposure causing PAM in this case. Conditions in the whitewater facility (warm, turbid water with little chlorine and heavy algal growth) rendered the water treatment ineffective and provided an ideal environment for N. fowleri to thrive. The combination of natural and engineered elements at the whitewater facility create a challenging environment to control the growth of N. fowleri . Disclosures: All authors: No reported disclosures.